Uji Aktivitas Anti-Inflamasi Minyak Atsiri Daun Kemangi (Ocimum americanum L.) pada Tikus Putih Jantan yang Diinduksi Karagenan - Saputri, Fadlina Chany; Zahara, Rita (UI Scholars Hub, 2016)
Kemangi (Ocimum americanum L.) is an aromatic plant that contains citral and known as anti-inflammatory agents. The aim of this study was to determine the anti-inflammatory activity of the essential oil kemangi leaves on carrageenan-induced rat. The male rats were divided into six groups, each consisting of four rats. Group I as negative control was given 0.5% CMC solution, group II as positive control was given diclofenac sodium, group III was given sitral, groups IV, V and VI were given 40 mg/200 g BW, 80 mg/200 g BW, and 160 mg/200 g BW essential oil of Ocimum americanum L., emulsified in 0.5% CMC solution. After 30 minutes of test substance administration, left paw of rats injected by 0.2 mL of carrageenan to induce edema. Edema volume was measured using pletismometer every hour for six hours. The result showed that at dose 160 mg/200 g BW gives the best effect in inhibited the inflamation response 44,83%. There was significant difference (p < 0.05) at dose 160 mg/200 g BB to negative control. From this study can be concluded that essential oil kemangi leaves has anti-inflammatory activity.